KLASTERISASI KERANJANG BELANJA TRANSAKSI PENJUALAN DENGAN MENGGUNAKAN K-MEANS CLUSTERING - Parasian D.P Silitonga; Misalina Ginting (Jurnal Mantik Penusa, 2018)
Shopping cart management systems in shopping centers are still done by remembering the sales history of each member. If the members handled are still small, of course this is not an obstacle. In addition to this, the system presented cannot know for certain the member who buys goods with certain types of categories, or the combination between the categories of goods. To be able to determine the right decision in recommending an item to a member, and also to find out how many members buy goods with a certain category, the company needs enough information to be able to do further analysis. Association rules on the K-Means algorithm are used to find relationships between data or how a group of data affects the existence of another data. This method can be used to help identify certain patterns in a large data set, and can be used to improve the marketing strategy of a shopping center. Keywords: Shopping Cart, Association Rule, K-Means Clustering.